Multiferroic behavior of Aurivillius Bi4Mn3O12 from first principles - Tinte, Silvia Noemi (2012)
The multiferroic behavior of the hypothetical Aurivillius compound Bi4 Mn3 O12 has been explored on the basisof density functional calculations. We ﬁnd that the tetragonal paraelectric phase of this material is ferromagnetic,showing ferroelectric and antiferrodistortive instabilities similar to the ones observed in its ferroelectric parentcompound Bi4 Ti3 O12 . Our results indicate, however, that the presence of Mn+4 ions at the B sites shrinks the cellvolume and, consequently, the unstable polar mode, associated with the ferroelectric polarization, is overcomeby an antiferrodistortive distortion. In this way, Bi4 Mn3 O12 exhibits incipient ferroelectricity at its equilibriumvolume. We show that the ferroelectric state can be favored by strain or partial substitution of Mn with Ti.